Safety Culture Education and Training in the Republic of Belarus - T. N. Korbut; A. V. Kuzmin; O. A. Nautsyk; D. A. Kuzmuk (Глобальная ядерная безопасность)
Safety culture education and training for managers and specialists is one of the most important tools for safety culture implementation and enhancement at nuclear facilities. In this article, the authors consider the topic of safety culture education in the Republic of Belarus. An analysis of the scope of the concept of «safety culture» application in the regulatory documentation of the Republic of Belarus and the IAEA is carried out. The requirements of the current rules and regulations of the Republic of Belarus regarding the development of safety culture among nuclear facilities employees, as well as international standards and recommendations of the IAEA on maintaining and improving the level of safety culture are given. Two directions of safety culture education in the Republic of Belarus are considered: education within the framework of the master’s program preparing young specialists and within the framework of advanced training courses for nuclear facilities employees, as well as a summary of these programs.